A Cost-Effectiveness Analysis of the Swedish Universal Parenting Program All Children in Focus - Ulfsdotter, Malin (PLoS One, 2015)
OBJECTIVE: There are few health economic evaluations of parenting programs with quality-adjusted life-years (QALYs) as the outcome measure. The objective of this study was, therefore, to conduct a cost-effectiveness analysis of the universal parenting program All Children in Focus (ABC). The goals were to estimate the costs of program implementation, investigate the health effects of the program, and examine its cost-effectiveness. METHODS: A cost-effectiveness analysis was conducted. Costs included setup costs and operating costs. A parent proxy Visual Analog Scale was used to measure QALYs in children, whereas the General Health Questionnaire-12 was used for parents. A societal perspective was adopted, and the incremental cost-effectiveness ratio was calculated. To account for uncertainty in the estimate, the probability of cost-effectiveness was investigated, and sensitivity analyses were used to account for the uncertainty in cost data. RESULTS: The cost was €326.3 per parent, of which €53.7 represented setup costs under the assumption that group leaders on average run 10 groups, and €272.6 was the operating costs. For health effects, the QALY gain was 0.0042 per child and 0.0027 per parent. These gains resulted in an incremental cost-effectiveness ratio for the base case of €47 290 per gained QALY. The sensitivity analyses resulted in ratios from €41 739 to €55 072. With the common Swedish threshold value of €55 000 per QALY, the probability of the ABC program being cost-effective was 50.8 percent. CONCLUSION: Our analysis of the ABC program demonstrates cost-effectiveness ratios below or just above the QALY threshold in Sweden. However, due to great uncertainty about the data, the health economic rationale for implementation should be further studied considering a longer time perspective, effects on siblings, and validated measuring techniques, before full scale implementation.